Unlocking the Past to Re-enact Rotterdam’s future: A professional’s view on planning history. - Arts, Martin (International Planning History Society Proceedings, 2016)
To implement policy, spatial planners depend on common narratives. That is true in Rotterdam too. But what sets a city like Rotterdam apart is that its history is influenced by dramatic and traumatic events. This history must therefore first be unlocked before we are able to design a successful future. The history of the last 140 years of port city of Rotterdam shows that, efforts were directed unilaterally on the port. This was due to the absence of a representative city. One consequence is that the city and the port are seen as two entities or stronger Rotterdam is mainly seen as a gateway. Today a new perspective for the port is badly needed, given the vulnerable position of a future without fossil fuels. That's why in 2013 the OECD argued that huge economic benefits could be achieved if the ports and cities worked together more effectively. However, to accept this challenging advice, the question is: “How can Rotterdam strip its historical grown lock-in, of the big port with a small city and look for a more synergetic future?’ Additionally the real potential of the social-economical interface of the port city region had not been explored.. The international Isocarp congress 2015 was an opportunity to re-enact Rotterdam’s future by bringing together experts from municipalities, port authorities and universities. . The idea was to research the impact of this international orientated port embedded in the local social-economic network or: “How to develop unprecedented port city synergy?”. It became clear that parallel histories of other port cities could be imaginaries for the future of Rotterdam. They show that a successful port can in fact boost an urban economy. However these histories can only shape the future by acting. Therefore the workshop was intended as a stepping-stone to re-enact the future. This paper will show that the synergy can only be successful when focussing on the Metropolitan region as a whole hosting the maritime and food cluster and knowledge and innovation hubs.